Innovative Strategies in English teaching and learning processes in secondary school - Narvaez Zelaya, Cindy Junieth | Vanegas Lara, Kiara Iberisse | Saavedra López, Darling Saavedra López Darling (UNAN-Managua, FAREM, Carazo , Nicaragua, 2019)
In secondary schools students start to learn English as a second language and because of this, the creation of innovative strategies are necessary in order to help them in the development of the language skills and sub skills, especially in the acquisition of vocabulary due to the large amount of words that are very frequently emphasized in books and verbal communication. For this reason, a proposal which is to implement Pictionary Games as an innovative strategy to improve vocabulary sub skill has been carried out with students of 10th grade “C” at Instituto Manuel Hernandez Martinez in Jinotepe-Carazo during the first semester 2019. The total of participants was forty-one students. Besides, this research includes data gathered from evaluation instruments such as: diagnostic test, survey, interviews and evaluation rubric. That valuable data was processed, analyzed and strongly considered when developing this research. The main objective of this research is to implement Pictionary Games more frequently for teaching the English language, since through the implementation of it, satisfactory results were obtained and they indicate that the students’ vocabulary knowledge improved. So, based on these results, it is also found that this strategy is really useful and facilitates the teaching-learning process in a meaningful way improving the English acquisition as a second language. Key words: English, innovative, strategies, vocabulary, Pictionary, games.